Prevalence of coccidia in domestic pigeons (Columba livia domestica Gmelin, 1789) in Benghazi city, Libya - Samira Al-Agouri; Nadia Alrwab; Hussien Amgawer; Ghazala Sadaga; Mohamed Idris Alshelmani (Aceh Journal of Animal Science, 2021)
Pigeon coccidiosis is caused by Eimeria spp; a protozoan parasite which limits birds’ productivity by causing severe illness. The current study was carried out to investigate the prevalence of coccidiosis on domestic pigeon in Libya. Intestinal contents of 100 pigeons (Columba livia domestica Gmelin, 1789) were collected within a period of five months; January to May 2020. The intestinal content was examined to detect of coccidian oocysts infection on the randomly selected birds. A total of 100 faecal samples were investigated with two methods;Willis-Schaafs (qualitative) and McMaster’s (quantitative). The results obtained showed that the number of infected Pigeons was 72 pigeons (72%) of the total number of Pigeons. The prevalence was higher in female than that of males, where the total of infected females was 50 (69.4 %) and infected males was 22 (30.6%). The results showed that the highest incidence of Eimeria labbeana was observed in the young pigeons than that of adults, where the total number of young pigeons was 66 (91.7 %), and adult pigeon was 6 (8.3 %).